Cyclic AMP and calcium signaling are involved in antipsychotic-induced diabetogenic effects in isolated pancreatic β cells of CD1 mice - Al-Ghafari, Ayat; Elmorsy, Ekramy Mahmoud; Al Doghaither, Huda; Fahmy, Eslam; Editor (International Journal of Health Sciences, 2022)
Objectives: Antipsychotics (APs) are medications used for different psychological disorders. They can introduce diabetogenic effects through different mechanisms, including cyclic AMP (cAMP) and calcium (Ca2+) signaling pathways. However, this effect is poorly understood. Therefore, this study aimed to evaluate the effect of three widely used APs [chlorpromazine (CPZ), haloperidol (HAL) and clozapine (CLZ)] on cAMP and Ca2+ signaling. Methods: The local bioethics committee of Northern Border University approved the study. Pancreatic β-cells were isolated from male CD1 mice, and three drug stock solutions were made in different concentrations (0.1, 1, 10 and 100 µM). The levels of glucose-stimulated insulin secretion (GSIS) and cAMP as well as the activities of adenylyl cyclase (AC), cAMP-dependent protein kinase (PKA), guanine-nucleotide exchange protein activated by cAMP (Epac 1 and 2), Ca2+ mobilization and Ca2+/calmodulin kinase II (CaMKII) were then determined using different methods. Results: APs were found to be cytotoxic to pancreatic ꞵ cells and caused a parallel and significant decrease in GSIS. APs significantly reduced the levels of cAMP in the treated cells, with an associated reduction in ATP production, CaMKII, PKA and transmembrane AC activities as well as Ca2+ mobilization to variable extents. In addition, the gene expression results showed that APs significantly decreased the expression of both the active subunits AC1 and AC8, the PKA α and β subunits, Epac1 and Epac2 as well as the four main subunits of CaMKII to variable extents. Conclusion: AP-induced alterations in the cAMP and Ca2+ signaling pathways can play a significant role in their diabetogenic potential.